PERUBAHAN PENUTUPAN LAHAN KHDTK SAMBOJA BERDASARKAN PENAFSIRAN CITRA LANDSAT 7 ETM+ TAHUN 2010 DAN 2013 - Nanang Riana, Sri Endayani, Djumanis Derita (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
This study is to find closure on the land and floor area KHDTK Samboja changes and to find out the cause. Results from this study is expected to enrich the reference about the closing conditions far beyond the land especially for those in need especially for writers.. This study uses the interpretation method on screen digitization of Landsat 7 ETM + imagery coverage in 2010 and 2013 . Results from the interpretation then dioverlaykan the forest map and a map of East Kalimantan government administration .From the results showed that over the period 2010 to 2013, the change of land based on the calculation of the closure of changing area of 104.8 ha ( 3.38 % ) of the total area of 3206.2 ha area can be compared . Slowly closing the mengalai class changes in the form of addition of secondary forests dry land size 19.6 ha ( 0.61% ) , shrub size 14.0 ha ( 0.44 % ) , Agriculture plus tick size of 17.1 ha ( 0.53 % ) , Garden of 3.5 ha ( 0.11 % ) , and change the form of reductions in class extents occurred slowly closing the open land about the size of 54.2 ha ( 1.69 % ) . While that did not happen in the classroom changed slowly closing retreat and Transmigration .Monitoring of forest resources must continue to be done in support of sustainable forest planning pengelolaaan better and suitable provisions.